Say it like Obama and win! the power of speaking with purpose and vision - Leanne, Shel (McGraw Hill, 2012)
In speech after speech, Barack Obama fires up enthusiastic supporters with his inspiring vision, rousing rhetoric, and charismatic presence. His outstanding communication skills gave rise to an unprecedented political movement and launched him to the top of the world political stage. But inspiring and persuading millions isn't simply a product of innate ability. Barack Obama spent time and effort honing skills that have made him so successful. These techniques are vital not only in the political arena, but also for business executives, managers, and leaders from all walks of life. This book is about the art of persuasion, the power of presentation, and the most effective methods of communication. From building strong arguments and facing tough issues to inspiring a team or workforce to new levels of innovation and productivity, Say It Like Obama and Win! gives you the tools to instill positive change at every level of your organization by teaching you how to: - Make a strong first impression - Use body language and voice - Establish common ground - Gain trust and confi dence - Win hearts and minds - Drive your points home - Convey your vision through imagery and words that resonate - Build to a crescendo and leave a lasting impression Whether you're a manager, an executive, a public speaker, a business owner, or a community leader, Say It Like Obama and Win! provides you with presentation techniques that have inspired and mobilized audiences of every size